2009
DOI: 10.1021/la802534q
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Formation and Thermal Stability of 11-MUA SAMs on Au(111)/Mica and on Polycrystalline Gold Foils

Abstract: In this article we present a comprehensive study of 11-mercaptoundecanoic acid self-assembled monolayer (SAM) formation on gold surfaces. The SAMs were prepared in ethanolic solution, utilizing two different substrates: Au(111)/mica and polycrystalline gold foils. Several experimental methods (X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, and atomic force microscopy) reveal a well-defined SAM. The main focus of this work, however, was to test the stability of these SAMs by thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 31 publications
4
34
0
Order By: Relevance
“…Similar dehydrogenations of aliphatic carbon chains were reported for alkanethiols and mercaptanoundecanoic acids where, upon heating to $600 K, all chemisorbed alkanethiols began to produce hydrogen and yield carbon clusters on the surface [28,37,38]. The high temperature peak above 760 K being a result of sample holder degassing can be excluded since we did not observe this peak when performing experiments with a Au(1 1 1) surface that had not been exposed to OTTP.…”
Section: Adsorption and Thermal Decomposition Of Ottp On Ausupporting
confidence: 77%
See 3 more Smart Citations
“…Similar dehydrogenations of aliphatic carbon chains were reported for alkanethiols and mercaptanoundecanoic acids where, upon heating to $600 K, all chemisorbed alkanethiols began to produce hydrogen and yield carbon clusters on the surface [28,37,38]. The high temperature peak above 760 K being a result of sample holder degassing can be excluded since we did not observe this peak when performing experiments with a Au(1 1 1) surface that had not been exposed to OTTP.…”
Section: Adsorption and Thermal Decomposition Of Ottp On Ausupporting
confidence: 77%
“…The C1s binding energy has a maximum at 284.0 eV, and a considerable amount of carbons remain on the surface. It has been reported that a pure carbon film rich of sp linear chains could be formed by heating hydrocarbons in UHV and subsequently stabilized as all-carbon structures (polycumulenes or carbon clusters) [37,40]. Based on our XPS and TPD results, the existence of solid carbon after heating OTTP on Au(1 1 1) at 900 K implies that we can achieve a hydrogen-free carbon backbone using OTTP.…”
Section: Adsorption and Thermal Decomposition Of Ottp On Aumentioning
confidence: 52%
See 2 more Smart Citations
“…To understand these fundamental issues, STM has been used as one of the very powerful tools for visualizing the atomic-and molecular-scale surface structures of SAMs on metal surfaces, as demonstrated in many previous reports. [1][2][3][4][6][7][8][9][10][11][12][13][14][15][16][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Additionally, thermal desorption spectroscopy (TDS) 10,11,32,[34][35][36][37] and electrochemical measurements [38][39][40][41][42][43] are very useful techniques to investigate the adsorption conditions, thermal stability, and the electrochemical behavior and stability of SAMs. TDS measurements revealed that alkanethiol SAMs exist as a form of monomer (alkanethiolate), not dimers (dialkyl disulfides) derived from associa-tive reactions of the sulfur headgroups, 10,11,34,…”
mentioning
confidence: 99%